Performing Academic Services through Mobile Application Development: A Case of Saudi Electronic University - Jaber Al-Adwani, Samer Atawneh (International Journal of Advanced Science and Technology, 2020)
The Saudi Electronic University (SEU) is an integral part of the governmental universities in the Kingdom of Saudi Arabia, which uses a range of e-learning systems and provides several electronic services that aim at addressing several issues faced by academic members and administrative departments, such as the Banner system. This system is one of the global systems that is likely to be adopted by several universities as it manages data that is related to students and faculty manners and offers them the required academic services. Nonetheless, at critical periods especially during the start of each academic semester, students might face difficulties with such a system due to the large volume of students who are likely to access the system simultaneously. This may in fact prevent students from carrying out any further and important academic services, such as registering for the required courses. Therefore, there is an urge need to develop a counterpart application that supports as many students as possible in performing their academic activities and in reducing the difficulties that are possibly encountered when using the current system. In this paper,we have developed an alternative Android-based mobile application that enables students to register for their courses and perform different important academic services. For instance, adding or dropping courses, modifying their schedules, and calculating their tuition fees, through their own smartphones. It is found to be proven from the findings that the proposed mobile application is a user-friendly application and efficient in terms of security, performance and software quality attributes.